Measurements of a confined circular jet - Kaung Htike, San (2016)
This final year project, the study was done on the flow characteristics of a heated air jet from a circular nozzle of diameter 22mm into the confined chamber. In-house hot wire anemometry technique was used for experimental measurements. Mean and root mean square velocities of the air jet were measured in the stream wise direction at distances up to 20 nozzle diameters downstream of the flow. There were two phases in performing the experiments, firstly by using a single hot wire probe and then by a cross-wire probe. The experimental mean velocity profile was observed to have reach self-preservation almost immediately after the potential core of the flow which ended at x/d = 4. In contract to the mean velocity profile, the self-preservation for the Reynolds normal and shear stress profiles was not observed and indicated that the turbulent zone of the jet was not fully developed. The confined circular jet was found to have laminar initial condition which closely follow the Blasius solution for laminar flow along the flat plate. The mean velocity profile was found to have decay rate of 0.1775 and flow spread rate of 0.0924. The temperature analysis of the flow using cold wire technique was not carried out due to time constraint in this project.